Pranayama Sebagai Pengurangan Nyeri Menstruasi Pada Remaja Putri di SMK Baiturrahim - Nurbaiti Nurbaiti; Ria Febrina (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Dysmenorrhea is a pain in the lower abdomen during menstruation due to the increased production of prostaglandins and their release from the endometrium during menstruation, causing uncoordinated and irregular uterine contractions resulting in pain. The incidence of dysmenorrhea in women of reproductive age ranges from 45%-95%, and primary dysmenorrhea experienced by adolescent girls is 60%-75%. Dysmenorrhea problems experienced by young women feel uncomfortable, concentration decreases, tension and anxiety cause disruption of daily activities. Efforts to overcome menstrual pain can be done by breathing relaxation, currently, there are still many who do not know the technique of breathing relaxation, so the team provides education about techniques in breathing relaxation to reduce pain during menstruation. The purpose of this community service activity is to provide education to young women using a lecture, discussion, and question and answer approach, the media used in the form of leaflets, this activity was carried out on December 20, 2021. This activity was attended by 40 young women with a pretest score of 60% knowledge after Health education is carried out the results of knowledge of adolescent girls increased to 90% of adolescents understanding breathing relaxation to reduce pain in menstruation. Community service activities are carried out regularly to provide knowledge for young women about reproductive health so that young women can understand and maintain their reproductive health